DATA OF EMPLOYMENT AND UNEMPLOYMENT IN GREECE - Persefoni POLYCHRONIDOU; Katerina TSISINOU; Giannoula FLOROU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2016)
With the economic crisis of recent years there is a wider discussion on issues of employment and unemployment in Greece. Development, attracting new investments, creating new jobs, unemployment rates, brain drain are some of the issues that interests the political, economic and social carriers of the country. This paper presents data on employment and unemployment in Greece for the last decade. Under this framework, data are presented and the relevant findings are discussed.